Heschel’s "The Prophets" as an Interreligious Turning Point - Bondi, Dror (Studies in Christian-Jewish Relations, 2026)
This article argues that Heschel's rewriting of The Prophets (1962) in the 1950s constituted a decisive turning point in his thought. It examines this transformation from three complementary perspectives: (1) chronologically, situating the rewriting in relation to Heschel’s earlier works and to the development of his emerging interreligious relationships and involvement; (2) methodologically, in comparison with the phenomenological framework of the original dissertation; and (3) hermeneutically, through a close analysis of his biblical citations, with particular attention to his adoption and modification of the Christian translation, the Revised Standard Version. Accordingly, the article advances three central claims: First, The Prophets marked a significant stage in the emergence of a theological pluralism. Second, The Prophets introduced a new methodology centered on the distinctive voices of individual prophets, subtly reconfiguring the relationship between the text and its intended readers. Third, The Prophets revealed an emerging interreligious hermeneutical orientation in the text itself through the adoption and subtle modification of the RSV. Taken together, these developments demonstrate that The Prophets not only influenced Heschel’s later public activism but also provided the conceptual foundations for his participation in the Jewish–Christian encounter that culminated in Nostra Aetate. I am grateful to Susannah Heschel and Ethan Schwartz for their insightful comments; to the Heschel Archive at Duke University for access to archival materials; and to Yehuda Dov Ber Zirkind for generously sharing these materials. This study forms part of a broader research project on Heschel’s interreligious thought, undertaken during my appointment as Corcoran Visiting Professor at the Center for Christian-Jewish Learning, Boston College.